Perlindungan Konsumen dalam Jasa Penyeberangan Menggunakan Perahu Nelayan Ke Pulau Pandang Batu Bara Perspektif Maslahah Mursalah - Rima Syahyana; Rahmad Efendi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the implementation of consumer protection in ferry services using fishing boats to Pandang Island, Batu Bara Regency and review it from the perspective of maslahah mursalah. This study uses an empirical juridical method with a statutory, empirical and conceptual approach. Data were obtained through interviews, observations, documentation involving ferry service managers, service users, and related parties and documentation studies by reviewing, examining, and analyzing various documents related to the research object to obtain relevant data. The results of the study indicate that consumer protection has been implemented through the provision of life jackets, safety briefings, fare transparency, and attention to weather conditions. However, the implementation is not optimal due to limited safety facilities, the unavailability of life jackets for all passengers, lack of supervision, and the potential for excess passenger capacity. Viewed from the perspective of maslahah mursalah, this ferry service is basically permissible because it provides benefits to the community and the local economy. However, deficiencies in safety aspects have the potential to cause harm that is contrary to the objectives of sharia, especially hifz al-nafs and hifz al-mal. Therefore, it is necessary to improve safety standards, provide adequate facilities, limit passenger capacity, and have more effective supervision.